The Influence of Learning Media, Learning Motivation and Mathematics Communication on Mathematics Learning Outcomes - Hany, Bella Asista; Setyaningsih, Nining (Universitas Sebelas Maret, 2021)
This study aim to determine the relationship between the influence of learning media, learning motivation, and mathematics communication on student learning outcomes. Learning outcomes play an important role in shaping the quality of education today. Qualitative-correlation research was conducted on 215 randomly student populations. The number of samples was determined using Slavin's theory. Junior High School 2 Banyodono was chosen as the research location referring to the results of observations which showed the low scores of the students' final exams. The results showed that the variables had an influence on student learning outcomes of 12.7%, while the remaining 87.3 were influenced by other factors. Learning media, learning motivation, and mathematical communication provide unexpected data, which contributes to student learning outcomes and deserves to be investigated further in this article.